CEDAW and Women’s Intersecting Identities: A Pioneering New Approach to Intersectional Discrimination - Meghan Campbell (Revista Direito GV)
ABSTRACT CEDAW is committed to eliminating all forms of discrimination and achieving gender equality so that all women can exercise and enjoy their human rights. This article argues that this implicitly includes a commitment to understanding and addressing intersectional discrimination. Women experience disadvantage and discrimination based on their sex and gender and that is inextricably linked to other identities, factors and experiences such as a race and poverty. Under CEDAW, if sex and gender is one of the bases for the discrimination, it is necessary to examine how other identity and factors contribute to gender discrimination and inequality. The CEDAW Committee has been pioneering this approach in the General Recommendations, Individual Communications, Inquiry Procedure and Concluding Observations, but it has not been consistently applying this fluid and expansive approach. The article poses three complementary solutions to these inconsistencies: a transformative equality analytical framework, a General Recommendation on intersectionality and workshops and training for CEDAW Committee members.